Pembuatan Konten Instagram Menggunakan Aplikasi Canva PRO Sebagai Media Promosi Produk SentralIn - Zalfa Nursyahira Ramadhanita; Tri Ramadani Arjo; Dwi Sudjanarti (Proceeding Maritime Business Management Conference, 2024)
Instagram is one of the platforms used in promotion to attract the attention of potential customers.SentralIn is a new product that has not run any promotions, so its Instagram account has not been optimized. This research aims to design Instagram Feeds as a promotional media using the Canva PRO application on the SentralIn Instagram account. This research used the action research method. Data collection methods included interviews, observations, questionnaires and documentation. Respondents in this study were 1 business owner, 2 design experts, 2 expert marketers and 10 online shop owners. Measurement of design effectiveness was done using the EPIC Rate method with 4 indicators, namely Empathy, Persuasion, Impact and Communication. This analysis was conducted in 2 cycles. After distributing questionnaires, the EPIC average score in cycle 1 shows an value of 4.04 out of 5.0 in the effective category. In cycle 2, increased to 4.41 out of 5.0 in the very effective category. It can be concluded that the Instagram Feeds research design that has been made is worth publishing and is very effective as a promotional media. Therefore, it needs to be done regularly in creating relevant, interesting, and useful content to maintain followers effectively.